2021
DOI: 10.1007/s12325-021-01992-4
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Narcolepsy 1 and its Comorbidities: What Clinicians Need to Know

Abstract: Narcolepsy is a chronic neurologic disorder associated with the dysregulation of the sleep-wake cycle that often leads to a decreased quality of life and results in a considerable health burden. There is often a delay to diagnosis of narcolepsy, mainly due to the lack of recognition of this disorder. One of the main factors hindering the diagnosis of narcolepsy is the association of comorbidities, which include other sleep disorders, psychiatric disorders, cardiovascular disorders, and metabolic disorders. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
(250 reference statements)
0
6
0
Order By: Relevance
“…Previous studies [12][13][14] have shown that the decrease of the orexin A level in narcolepsy leads to decreased binding with receptors, weakening the activity of REM sleep inhibition brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [12][13][14] have shown that the decrease of the orexin A level in narcolepsy leads to decreased binding with receptors, weakening the activity of REM sleep inhibition brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…4 HLA DQB1*0602 is found in most of the patients with narcolepsy. 5 Narcolepsy may not always present with the typical triad of symptoms. Canellas et al reported a case series of Narcolepsy patients with psychosis and schizophrenia which posed a diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Modafinil (Provigil) and armodafinil (Nuvigil) are non-amphetamine central nervous system stimulants that can be used to treat excessive sleepiness caused by shift work sleep disorder. While modafinil is a racemic molecule, armodafinil is the (R)-enantiomer of modafinil [39]. Both medicines have the same pharmacologic qualities and are equally effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“…Both medicines have the same pharmacologic qualities and are equally effective and safe. Prenatal exposure to modafinil or armodafinil appears to raise the chance of significant congenital abnormalities, so these drugs should be avoided during pregnancy [39]. Modafinil inhibits dopamine and noradrenaline absorption in the region of the hypothalamus involved in sleep induction and is safer and more effective and less addictive than other central nervous system stimulants [40].…”
Section: Discussionmentioning
confidence: 99%